Rough Set Extension Model of Incomplete Information System - Yue Hou (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper investigated the incomplete information system in which situation of the more missing or absent unknown values. Based on the original characteristic relation, we proposed a new reflective relation which was controlled by the parameter alpha, beta. By analyzing illustrative examples and comparing to the original characteristic relation, this paper indicated the validity and practicability of the new-defined binary relation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4732